Transcranial Magnetic Stimulation Exerts “Rejuvenation” Effects on Corticostriatal Synapses after Partial Dopamine Depletion - Natale, Giuseppina; Pignataro, Annabella; Marino, Gioia; Campanelli, Federica; Calabrese, Valeria; Cardinale, Antonella; Pelucchi, Silvia; Marcello, Elena; Gardoni, Fabrizio; Viscomi, Maria Teresa; Picconi, Barbara; Ammassari‐Teule, Martine; et al. (Movement disorders, 2021)
Background In experimental models of Parkinson's disease (PD), different degrees of degeneration to the nigrostriatal pathway produce distinct profiles of synaptic alterations that depend on progressive changes in N‐methyl‐D‐aspartate receptors (NMDAR)‐mediated functions. Repetitive transcranial magnetic stimulation (rTMS) induces modifications in glutamatergic and dopaminergic systems, suggesting that it may have an impact on glutamatergic synapses modulated by dopamine neurotransmission. However, no studies have so far explored the mechanisms of rTMS effects at early stages of PD. Objectives We tested the hypothesis that in vivo application of rTMS with intermittent theta‐burst stimulation (iTBS) pattern alleviates corticostriatal dysfunctions by modulating NMDAR‐dependent plasticity in a rat model of early parkinsonism. Methods Dorsolateral striatal spiny projection neurons (SPNs) activity was studied through ex vivo whole‐cell patch‐clamp recordings in corticostriatal slices obtained from 6‐hydroxydopamine‐lesioned rats, subjected to a single session (acute) of iTBS and tested for forelimb akinesia with the stepping test. Immunohistochemical analyses were performed to analyze morphological correlates of plasticity in SPNs. Results Acute iTBS ameliorated limb akinesia and rescued corticostriatal long‐term potentiation (LTP) in SPNs of partially lesioned rats. This effect was abolished by applying a selective inhibitor of GluN2B‐subunit‐containing NMDAR, suggesting that iTBS treatment could be associated with an enhanced activation of specific NMDAR subunits, which are major regulators of structural plasticity during synapse development. Morphological analyses of SPNs revealed that iTBS treatment reverted dendritic spine loss inducing a prevalence of thin‐elongated spines in the biocytin‐filled SPNs. Conclusions Taken together, our data identify that an acute iTBS treatment produces a series of plastic changes underlying striatal compensatory adaptation in the parkinsonian basal ganglia circuit. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society